Production-inventory model with waiting time proportional to production time (2006)
In this paper we study a production model ¿inventory with constant demand and production rates. Within the assumptions it is considered that the waiting time, referred to the time in which the production unit is disabled, is proportional to the activity time of the same. The objective is to develop a mathematical model and determine the optimal number of cycles that minimize costs, or maximize utility.